Penerapan Tujuan Pembangunan Berkelanjutan (SDGs) dalam Sosial dan Ekonomi Dimediasi Reputasi, Kepercayaan dalam Organisasi Terhadap Loyalitas - Yanuar Rizky Saputro; Muzakar Isa (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research aims to analyze Sustainable Development Goals (SDGs) in social and economic dimensions on the reputation and trust of Islamic universities in Surakarta, as well as their impact on student loyalty. Through a quantitative approach, data was collected using questionnaires as a data collection technique. Statistical analysis was utilised to verify hypotheses in the course of data analysis. Socially and economically, the SDGs have a substantial impact on the reputation and trustworthiness of higher education, according to the findings of this study. The economic dimension of the SDGs also has a substantial influence on the reputation and trust of universities, whereas the social dimension of the SDGs contributes positively and significantly to that regard. Furthermore, reputation and trust have a positive and significant effect on student loyalty at Surakarta Islamic universities, according to the research findings. Therefore, the integration of SDGs in social and economic aspects can play a role in increasing reputation, trust, and ultimately, student loyalty towards Islamic universities in Surakarta.